2020
DOI: 10.1177/1054773820907757
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity Levels and Functional Capacity in Patients with Advanced Chronic Kidney Disease

Abstract: The purpose of this study is to assess whether the functional capacity of patients with chronic kidney disease stage V (CKD-5D) is different depending on their physical activity levels. We also compared functional capacity, quality of life, and symptoms of depression depending on treatment modalities (HD vs. PD). A Cross-sectional study included 52 patients (35HD and 17PD; males 61.5%, mean age 71 years). The main measurements were physical activity level using the Human Activity Profile questionnaire (HAP), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…As expected, the findings revealed that lower HAP was a determinant of impaired body structure and function, and reduced activity and social participation in HD patients. These findings reinforce those of Jimenez et al, who showed an association between HAP and functional capacity [38]. However, the fact that we included body Fig.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, the findings revealed that lower HAP was a determinant of impaired body structure and function, and reduced activity and social participation in HD patients. These findings reinforce those of Jimenez et al, who showed an association between HAP and functional capacity [38]. However, the fact that we included body Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It seems that the PA level also has an impact on physical function measured through physical performance tests (PPTs), as a study showed that patients on HD or PD with impaired PA measured through the adjusted activity score (AAS) of the Human Activity Profile (HAP) scale (<53 points) had worse physical function (walking capacity measured with the 6-min walking test, gait speed in 4 m, sit-to-stand-to-sit capacity, functional mobility as measured through the short physical performance battery) compared with patients who were moderately active or active (53–94 points) [ 9 ].…”
Section: Physical Inactivity Has An Important Negative Impact For Patientsmentioning
confidence: 99%
“…As a single tool, we would recommend the HAP (AAS) for dialysis patients, as it is inexpensive and simple to administer and it has proved to discriminate patients with worse physical function [ 9 ].…”
Section: What Measurement Tools To Measure Physical Activity?mentioning
confidence: 99%
See 1 more Smart Citation
“…PA level is lower in CKD patients at any stage compared to healthy counterparts 6 , 7 . It seems that PA level has also an impact on physical function since patients in HD or peritoneal dialysis with impaired PA had worst physical function compared with more active patients 8 , 9 . Several studies have recently been published which report the beneficial effects of exercise on the physical function of patients receiving HD 4 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%